'Hottest brand, coolest pedagogy': approaches to corporate branding in Singapore's higher education sector. Issue 1 (2nd January 2016) - NG, Carl Jon Way
ABSTRACT: This article examines the corporate branding efforts of Singapore's publicly funded higher education institutions within a context of neoliberal marketization. Adopting a discourse-analytic perspective, it examines the kind of branding approaches employed by Singapore's universities and polytechnics, and how these approaches are realized discursively in their brand artefacts. Three main approaches are identified and discussed. Referred to as (i) characterizing the brand; (ii) positioning the brand and (iii) personalizing the brand, they are constituted by a variety of language devices and discursive strategies such as positive evaluation, colloquial language and the use of particular metaphors, and represent a spread of approaches ranging from the more fact/reason-based to the experience/emotion-oriented. While the institutions employ a range of approaches, the findings of the analysis suggest that experience/emotion-oriented approaches are better elaborated in the artefacts, and gaining traction in the sector as a whole.